Career orientations and motivation of top and middle-level managers - Lyudmila D. Zheldochenko, Svetlana V. Zholudeva, Anna M. Sheveleva, Marina V. Naumenko, Irina A. Pankratova, Evgeny I. Rogov, (Opción, 2019)
The research is devoted to the motivation of specialists who achieved top positions in organizations. The paper researches career orientations and motivation of 135 managers of state enterprises. The methods used are the test for measuring the achievement motivation, the method of diagnosing satisfaction of basic needs, the authors’ questionnaire, and comparative analysis. As a result, the leading career orientations for the sample, in general, are Service and General managerial competence. In conclusion, the career orientation of General managerial competence tends to increase with the growth of success attainment motivation.